Values and Business Ethics in a textile company in La Victoria - Lima, 2024 - Aguilar Cordova, Carol Jimena; Quispe Huanca, Hector Luis (LACCEI, 2024)
This study investigated the relationship between values and business ethics in a textile company in La Victoria, Lima, in 2024. It was observed that companies in the textile sector improve the work environment by promoting an ethical organizational culture, essential for maintaining trust and long-term success. The research adopted a quantitative approach with a non-experimental descriptivecorrelational design. Surveys were conducted with 48 administrative employees, selected from a total population of 54 workers, using questionnaires as the instrument. The results showed a weak correlation (r = 0.211, p = 0.684) between values and business ethics according to Pearson's correlation test, leading to the rejection of the general alternate hypothesis. These findings highlight the importance of companies reinforcing their ethical practices. Fostering transparency, duty compliance, respect for organizational values, and adopting a proactive approach to business ethics are essential for preserving trust and reputation in the workplace and commercial realm.